Downregulation of serum vitamin D receptor level, serum 25-hydroxyvitamin D, and association of vitamin D receptor gene polymorphisms ApaI and TaqI with obesity in the Bangladeshi population - Annur Ferdous; Munira Jahan Raisa; Md Hijbullah; Nafiz Imtiaz Siam; Shatabdy Barua Trisha; Sadia Biswas Mumu; Md Aminul Haque; Javed Ibne Hasan; Muhammed Mahfuzur Rahman; Md Shaki Mostaid (PLoS ONE, 2025)
Background/Objectives Obesity is a chronic metabolic disorder, and its prevalence in Bangladesh is increasing at an alarming rate. Previous reports have suggested a significant association between Vitamin D receptor (VDR) gene polymorphisms and obesity, but with inconsistent results. The purpose of our study was to investigate the association between two single-nucleotide polymorphisms (SNPs) (Apal, rs7975232, and Taql, rs731236) of the VDR gene and the risk of obesity in the Bangladeshi population. Moreover, we looked at serum VDR levels and serum 25-hydroxy vitamin D levels in people with obesity (n = 124) and healthy controls (n = 126). Methods Genotyping was performed using Polymerase Chain Reaction-Restriction Fragment Length Polymorphism (PCR-RFLP). General linear model and multivariate logistic regression analysis were used to calculate the adjusted odds ratio (OR) along with 95% confidence intervals (CI) and P-values. Results Serum VDR level was downregulated in people with obesity compared to healthy controls (P < 0.0001) along with significantly lower levels of 25-hydroxy vitamin D (P < 0.0001). For the ApaI rs7975232 (C > A) polymorphism, the CA Heterozygous genotype carried a 1.93-fold higher risk of developing obesity (OR=1.93, 95% CI = 1.10–3.41, P = 0.023). On the contrary, for TaqI, rs731236 (T > C), no significant association was found for both heterozygous and mutant homozygous genotypes. Conclusion We report the downregulation of serum VDR levels and serum 25-hydroxy vitamin D levels in people with obesity. Moreover, a polymorphism of Apal (rs7975232 C > A) in the VDR gene increases the risk of developing obesity in the Bangladeshi population.